Making millions the easy way - Gibbon, Johanna; BBC worldwide (North Sydney, NSW : BBC Worldwide, 2003)
This is the story of how teams of students from the world's famous mathematical institution systematically set out to break the casinos of Las Vegas
Title from title screen
Editor, Matthew, Barrett ; sound, Ben Quinn
Narrator: John Simm
DVD format
Keywords: Massachusetts Institute of Technology -- Students; Cardsharping; Gambling -- Nevada -- Las Vegas; Gamblers -- Massachusetts -- Boston